Respuesta del crecimiento de plántulas de arroz en macetas a la aplicación de cuatro grupos de bioestimulantes - Zambrano Alcívar, Fabián Enrique (2019)
The main objective of the research was to analyze the growth response in rice seedlings in pots to the application of four groups of biostimulants. The work was developed during the dry season of 2019 on the ESPAM MFL campus. The groups of biostimulants tested were algae extract, phytohormones, bioactivators and organic acids, within which three commercial products were evaluated. The experimental design used was the completely randomized group, with thirteen treatments, three replicates and 39 experimental units. The main variables evaluated were dry weight, leaf area, relative growth rate (RGR) and net assimilation rate (NAR). The data were subjected to analysis of variance and orthogonal contrasts, and the separation of means with Tukey's test at 5% probability of error. No significant differences (p>0.05) were found between biostimulants and within biostimulant groups. However, the orthogonal contrast analysis between the biostimulant and control groups showed significant differences (p<0.05), where all the biostimulant groups evaluated statistically exceeded the control treatment, both in dry weight, foliar area, RGR and NAR. Biostimulant groups based on extracts of algae, phytohormones and bioactivators showed the highest growth rates in terms of dry weight, leaf area, RGR and NAR.